ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA SINEI KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG - Galib Kaninu, Fitriana (AGROTEKBIS, 2016)
Sinei village is a village located in the district of South Tinombo which has rice production is quite large compared to other villages located in the district of South Tinombo. The amount of rice production obtained not guarantee high incomeÂ received by farmers. Rice production obtained in the village of Sinei relatively high, does not mean the income is also high, so it needed a revenue analysis and feasibility study farmingÂ rice paddy fields in the village of Sinei.Â revenueÂ aims to determine the amount of income and the feasibility of paddy rice farming conducted in January to the month of March 2015. Location determination is done intentionally (purposive) with the consideration that Sinei village is one of the producing areas of paddy with productivity of 4.11 tonnes /ha. The analysis used in this study is an analysis of earnings (Ï) and feasibility (a). Results of the analysis showed that the average income of rice farmers for the planting seasons in the Sinei village subdistrict of South Tinombo Parigi Moutong district is Rp 6.081.909,63/1,05 ha/MT or USD 5.792.294,88Â ha/MT. The analysis showed Revenue Cost Ratio of paddy rice farming obtained by 1.84, thus, paddy rice farming in the Sinei village worth the effort, because the value of a ratio > 1.